UNIQUE DENSITY PROFILE DETERMINATION IN THIN-FILMS - Penfold, J; Webster, J; Bucknall, D; Sivia, D (1994)
A recent paper by D.S. Sivia and R. Pynn (SPIE Conf. Proc., Vol. 1738, 1992) has shown theoretically the use of polarised neutrons and a magnetised substrate to determine uniquely a density profile from neutron reflectometry data. Presented here are preliminary results of the technique applied to a polymer film on a magnetised nickel substrate. © 1994.